A preparation method of silicon-based magnetic beads and chemiluminescence application

By adopting a sandwich structure, the silicon-based magnetic beads are solved by using layer-by-layer self-assembly method and surface encapsulation technology, the problems of existing magnetic microspheres are high nonspecific and environmental pollution in in vitro diagnosis, and the preparation of low nonspecific, high sensitivity and multifunctional magnetic beads is achieved, which is suitable for chemiluminescence applications.

CN119775999APending Publication Date: 2025-04-08常州伯仪生物科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411980263.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing magnetic microspheres have high nonspecific, false positive or false negative problems in in vitro diagnosis, and the use of organic reagents during production leads to environmental pollution, and the product types and applications are relatively single.

Method used

Silicon-based magnetic beads with sandwich structure are composed of silica microsphere core, magnetic particle layer, silica outer layer coating and carboxy modified layer. They are prepared by layer self-assembly method and surface encapsulation technology to ensure stable coating of magnetic particles.

Benefits of technology

It achieves low nonspecificity, high sensitivity and stability, reduces environmental pollution, and provides products of various sizes, suitable for chemiluminescence applications, and has long shelf life and high yields, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775999A_ABST
    Figure CN119775999A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of bio-separation materials, and in particular to a method for preparing silicon-based magnetic beads and chemiluminescent applications. The present invention provides a method for preparing silicon-based magnetic beads, comprising the following steps: (1) preparing a silicon dioxide microsphere core; (2) preparing dithiothiocarbazine DMSA-coated aqueous phase particles; (3) preparing magnetic microspheres by layer-by-layer self-assembly; (4) surface silicon dioxide encapsulation; (5) surface carboxyl modification to obtain silicon-based magnetic beads. It has low nonspecificity and high sensitivity, small batch-to-batch differences, and reproducible results. It can provide a variety of sizes to meet the needs of different projects, and is an ideal choice for chemiluminescent applications. The product development steps follow the green environmental protection principle, do not contain plastic particles, and are beneficial to environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biological separation materials, and in particular to a preparation method of silicon-based magnetic beads and chemiluminescence applications. Background Art

[0002] In recent years, plastic pollution has been one of the most serious environmental problems facing mankind and one of the important issues of concern to the United Nations Environment Programme. According to data released by the agency, humans currently produce more than 400 million tons of plastic each year, which is about three times that of 2021. According to statistics, the amount of plastic waste generated and processed by research laboratories around the world is as high as 15 million tons.

[0003] Magnetic microspheres are commonly used materials for in vitro diagnosis. They are generally composed of magnetic particles and organic polymers (polystyrene PS, polymethyl methacrylate PMMA, etc.). In order to balance the needs of quality and environmental protection, foreign biomaterial companies have begun to adopt green design from production to customer end to prepare magnetic microspheres without organic polymers. For example, Invitrogen TM DynaGreen TM Magnetic beads. But DynaGreen TM Magnetic beads only have one particle size of 250nm, and are only used for protein A and protein G. (Source: Thermo Fisher Scientific official website) The product types and applications are relatively simple.

[0004] Patent CN116626289A provides a sandwich-type magnetic microsphere, which adopts a swelling method similar to Dyna. The base ball is a polystyrene microsphere. The swelling process requires organic reagents, which poses environmental problems. In addition, the transmission electron microscope TEM images in the patent show that the magnetic particle loading is low, the saturation magnetization intensity VSM is less than 10emu / g, and the magnetic responsiveness is weak. Although the microspheres with low magnetic content have better suspension properties, the separation time is long, which affects the detection efficiency.

[0005] Here we provide a sandwich structure carboxyl silica magnetic beads, which are composed of a silica microsphere core, a magnetic particle layer, a silica outer layer coating and a carboxyl modified layer, such as Figure 1 As shown. Low non-specificity, high sensitivity, small batch-to-batch differences, and reproducible results. Available in a variety of sizes to meet the needs of different projects, it is an ideal choice for chemiluminescence applications. The product development steps follow the green environmental protection principle, do not contain plastic particles, and are beneficial to environmental protection. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing environmentally friendly silicon-based magnetic beads and chemiluminescent applications.

[0007] The technical solution of the present invention to solve the above technical problems is as follows:

[0008] A method for preparing silicon-based magnetic beads comprises the following steps:

[0009] (1) Preparation of the core of silica microspheres;

[0010] (2) Preparation of aqueous phase particles coated with dithiosuccinic acid (DMSA);

[0011] (3) Preparation of magnetic microspheres by layer-by-layer self-assembly method;

[0012] (4) Surface silica encapsulation;

[0013] (5) Surface carboxyl modification to obtain silica-based magnetic beads.

[0014] Preferably, the step (1) of preparing the inner core of the silica microspheres comprises: The silica microspheres are prepared by the seed growth method and the sintering method; the particle size of the silica microspheres is 200nm-3μm.

[0015] Preferably, the particle size of the silica microspheres is 400 nm-1.5 μm.

[0016] Preferably, the preparation of aqueous phase particles in step (2) includes preparing oleic acid-coated magnetic particles and DMSA-coated aqueous phase particles by coprecipitation; the coprecipitation method for preparing oleic acid-coated magnetic particles includes mixing and dissolving ferric chloride hexahydrate, ultrapure water, and ferrous sulfate heptahydrate, heating to 70-75°C, adding ammonia water, keeping warm for 20-60 minutes, adding oleic acid, continuing the reaction for 20-60 minutes, heating to 80-85°C, aging for 1-2 hours, magnetically separating the product, and dispersing it in n-hexane to form a 50-100 mg / mL magnetic fluid solution.

[0017] Preferably, the preparation of the DMSA-coated aqueous phase particles includes mixing acetone, n-hexane, and dimercaptosuccinic acid, adding an oleic acid-coated magnetic particle fluid solution, refluxing the reaction for 4-5 hours, magnetically separating the product, dispersing it in ultrapure water, adjusting the pH to 9.5-10, ultrasonicating for 20-60 minutes, adjusting the pH to neutral, ultrasonicating for 20-60 minutes, filtering, and obtaining DMSA-coated aqueous phase particles.

[0018] Preferably, in the step (3), the layer-by-layer self-assembly method for preparing magnetic microspheres comprises: 1) mixing the 5-10 mg / mL polyethyleneimine aqueous solution with the 3M NaCl solution, adding the silica microsphere core aqueous solution of step (1) thereto, ultrasonicating for 30-60 min, centrifuging and washing with water, to obtain magnetic microspheres coated with positive electrolytes.

[0019] Preferably, in the step (3), the layer-by-layer self-assembly method for preparing magnetic microspheres also includes the step 2) mixing the DMSA-coated aqueous particles with a 3M NaCl solution, adding the solution to the positive electrolyte-coated magnetic microspheres, ultrasonicating at 400-500 rpm for 20-60 min, centrifuging and washing with water to obtain a layer of Fe3O4-coated microspheres, repeating the above steps 1) and 2) until 5 layers of Fe3O4 are coated, thereby obtaining magnetic microspheres prepared by the layer-by-layer self-assembly method.

[0020] Preferably, the surface silica encapsulation in step (4) comprises adding ammonia water and tetraethyl orthosilicate (TEOS) to the magnetic microspheres obtained in step (3), reacting at 20-35° C. for 2-2.5 hours, and magnetically separating to obtain a surface silica encapsulated product.

[0021] Preferably, the surface carboxyl modification in step (5) also includes surface amino modification before the surface carboxyl modification, and the surface amino modification material is one or more of triaminopropyltriethoxysilane APTES and polyethyleneimine PEI; the surface carboxyl modification includes coupled polyacrylic acid PAA and succinic anhydride modification.

[0022] Preferably, the silica-based magnetic beads obtained by the preparation method are used in CA242 chemiluminescence platform, nucleic acid extraction, and DNA fragment sorting.

[0023] The beneficial effects of the present invention are as follows: the prepared silicon-based magnetic beads have low non-specificity and high sensitivity, high stability, small batch-to-batch differences, and reproducible results. A variety of sizes can be provided to meet the needs of different projects, and are ideal for chemiluminescence applications. The structure is environmentally friendly, using a non-organic polymer silica microsphere core. The application solves the defects of existing products and avoids high non-specificity, false positives or false negatives. The shelf life is long, the yield is high, and large-scale production can be achieved. The product development steps follow the green environmental protection principle, do not contain plastic particles, and are beneficial to environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of the silicon carboxyl magnetic microspheres of the present invention;

[0025] Figure 2 It is the real object photo and magnetic separation effect diagram of Example 1;

[0026] Figure 3 This is a scanning electron microscope image of Example 1;

[0027] Figure 4 This is a scanning electron microscope image of Example 2;

[0028] Figure 5 This is a scanning electron microscope image of Example 3;

[0029] Figure 6 This is a scanning electron microscope image of comparative example 1;

[0030] Figure 7 is a graph showing the test results of the SEPMAG biomagnetic separator of Example 1;

[0031] Figure 8 This is a graph showing the result of the ninhydrin colorimetric reaction of the intermediate amino ball of Example 1;

[0032] Fig. 9 It is a diagram of the color development reaction results of tetramethylbenzidine TMB in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below with reference to the embodiments, but is not limited thereto.

[0034] Example 1: This example provides a method for preparing 500nm silica carboxyl magnetic microspheres, which specifically includes the following steps:

[0035] (1) Preparation of 400nm silica microsphere core

[0036] Mix 73.8 mL of ethanol, 10.8 mL of deionized water, and 9.8 mL of ammonia water in a 250 mL three-necked flask, add 5.6 mL of tetraethyl orthosilicate TEOS, heat in a 30° water bath, and react for 12 hours under stirring conditions of 500 rpm. The product is centrifuged and ultrasonically dispersed (with ethanol) 4 times, and then centrifuged and ultrasonically dispersed (with water) 4 times. Silica microspheres with a size of about 400 nm are obtained.

[0037] (2) Preparation of aqueous magnetic particles

[0038] 1) Preparation of oleic acid (OA)-coated magnetic particles (Fe3O4@OA) by coprecipitation

[0039] In a 250mL three-necked flask, add 50g of solid ferric chloride hexahydrate (FeCl3·6H2O), 150mL of ultrapure water, and 30g of solid ferrous sulfate heptahydrate (FeSO4·7H2O) in sequence, and stir ultrasonically to dissolve it completely. Heat in a water bath under nitrogen and condensed water conditions to 72°C. Pour in 80mL of ammonia water while stirring at 500rpm. React at 72°C for 30 minutes, add 15mL of oleic acid, continue to react for 30 minutes, then heat to 85°C and mature for 1 hour. After cooling, the product is magnetically separated, washed repeatedly with ethanol and ultrapure water, and dispersed in 200mL of n-hexane to form a stable magnetic fluid solution.

[0040] 2) Preparation of aqueous phase particles coated with dithiosuccinic acid (DMSA)

[0041] Add 320mL acetone, 220mL n-hexane, 2.5g DMSA to a 1000mL three-necked flask, stir to dissolve, then add 100mL of the oil phase magnetic particle solution prepared in the previous step. Place in a 60℃ water bath, stir at 500rpm, condense and reflux, and react for 4 hours. After the product is cooled, wash it 10 times with magnetic separation ultrapure water until the supernatant is clear. Disperse in 1L ultrapure water, add sodium hydroxide solution to adjust the pH to 10, and sonicate for 30 minutes to stabilize the pH at 10. Use dilute hydrochloric acid solution to adjust the pH to neutral, and sonicate for another 30 minutes. Pass through a 0.22μm filter membrane. Store at 4℃ away from light.

[0042] (3) Preparation of magnetic microspheres by layer-by-layer self-assembly method:

[0043] 1) 300 mL of polyethyleneimine PEI solution (5 mg / mL) and 25 mL of 3M NaCl solution were added to a 1 L three-necked flask, placed in an ultrasonic cleaner, and mechanically stirred at 500 rpm. 100 mL of 400 nm silica microsphere solution obtained in step (1) was added dropwise to the PEI solution. Ultrasonication was performed for 45 minutes. The solution was centrifuged and washed 4 times at 8000 rpm for 5 minutes. Magnetic microspheres coated with positive electrolyte PEI were obtained.

[0044] 2) Add 200 mL of DMSA-modified Fe3O4 aqueous solution (10 mg / mL) and 25 mL of NaCl solution into a 1L three-necked flask, add 200 mL of microspheres obtained by centrifugation in the previous step into the Fe3O4 solution under ultrasonic stirring, stir at 500 rpm for 45 minutes, and wash the product by centrifugation at 8000 rpm for 5 minutes until the supernatant is colorless and transparent. A layer of Fe3O4-coated microspheres is obtained.

[0045] Repeat the above steps 1) and 2) until 5 layers of Fe3O4 are coated and dispersed in ultrapure water to obtain an aqueous solution of SiO2@Fe3O4 microspheres.

[0046] (4) Surface silica encapsulation:

[0047] 200mL ethanol, add 20mL Fe3O4 microsphere aqueous solution obtained in the previous step, stir at 300rpm for 15 minutes under ultrasound, add 5mL ammonia water, continue ultrasound for 15 minutes, add 10mL tetraethyl orthosilicate TEOS, react in a 30℃ water bath, stir at 300rpm for 2 hours. The product is magnetically separated, washed 4 times with anhydrous ethanol and water respectively. Dispersed in anhydrous ethanol.

[0048] (5) Surface carboxyl modification:

[0049] 1) Surface amino modification (anhydrous ethanol system)

[0050] Aminosilane, triaminopropyltriethoxysilane (APTES) was selected as the modified material. The microspheres obtained in the previous step were dispersed in 200 mL of anhydrous ethanol, 5 mL of ammonia water was added, and stirred at 300 rpm for 15 minutes under ultrasound. 2 mL of APTES was added and reacted at 30 ° C and 300 rpm for 18 hours. Magnetic separation, anhydrous ethanol washing 4 times and water washing 4 times. The product was dispersed in pure water.

[0051] 2) Surface carboxyl modification (coupling polyacrylic acid PAA)

[0052] Add 1ml polyacrylic acid PAA and 80ml water to the 20ml amino ball obtained in the previous step, place it in a 500ml three-necked flask and stir at 320rpm for 30min, wash it with water, wash it with MES buffer, resuspend it with 80ml MES, add 20ml MES solution of 100mg EDC under ultrasonic for 3min, react at 37℃ for 2h, add 15ml ethanolamine solution to seal for 30min. Wash it with water and separate it magnetically, adjust the pH to 7 and wash it with water again. The final product, silica carboxyl magnetic microspheres, is dispersed in pure water. Figure 2 It is the real object photo and magnetic separation effect diagram of embodiment 1.

[0053] Example 2: This example provides a method for preparing 1 micron silica carboxyl magnetic microspheres, comprising the following steps:

[0054] (1) Preparation of 800 nm silica microsphere cores by seed growth method

[0055] In a 1000mL three-necked flask, first mix 252mL of methanol, 65mL of deionized water, and 20mL of ammonia water, and stir mechanically (speed 500rpm). Add 3.125g of the 400nm SiO2 microsphere suspension prepared in Example 1 (the specific concentration needs to be calculated, about 3×10 10 SiO2 microspheres / L). Then, under mechanical stirring and ultrasonic treatment, ammonia / water / methanol mixed solution (30.5 / 17.5 / 52mL, 100mL in total) and TEOS / methanol mixed solution (81.5 / 18.5mL, 100mL in total) were added dropwise using two syringe pumps, with a dropwise speed of 1ml / min. After the dropwise addition, the reaction was continued for 2h; after centrifugal washing, it was dispersed in ethanol. 800nm ​​silica microspheres were obtained.

[0056] (2) Preparation of aqueous magnetic particles

[0057] 1) Preparation of oleic acid (OA)-coated magnetic particles (Fe3O4@OA) by coprecipitation

[0058] In a 250mL three-necked flask, add 50g of solid ferric chloride hexahydrate (FeCl3·6H2O), 150mL of ultrapure water, and 30g of solid ferrous sulfate heptahydrate (FeSO4·7H2O) in sequence, and stir ultrasonically to dissolve it completely. Heat in a water bath under nitrogen and condensed water conditions to 72°C. Pour in 80mL of ammonia water while stirring at 500rpm. React at 72°C for 30 minutes, add 15mL of oleic acid, continue to react for 30 minutes, then heat to 85°C and mature for 1 hour. After cooling, the product is magnetically separated, washed repeatedly with ethanol and ultrapure water, and dispersed in 200mL of n-hexane to form a stable magnetic fluid solution.

[0059] 2) Preparation of aqueous phase particles coated with dithiosuccinic acid (DMSA)

[0060] Add 320mL acetone, 220mL n-hexane, 2.5g DMSA to a 1000mL three-necked flask, stir to dissolve, then add 100mL of the oil phase magnetic particle solution prepared in the previous step. Place in a 60℃ water bath, stir at 500rpm, condense and reflux, and react for 4 hours. After the product is cooled, wash it 10 times with magnetic separation ultrapure water until the supernatant is clear. Disperse in 1L ultrapure water, add sodium hydroxide solution to adjust the pH to 10, and sonicate for 30 minutes to stabilize the pH at 10. Use dilute hydrochloric acid solution to adjust the pH to neutral, and sonicate for another 30 minutes. Pass through a 0.22μm filter membrane. Store at 4℃ away from light.

[0061] (3) Preparation of magnetic microspheres by layer-by-layer self-assembly method:

[0062] 1) 300 mL of polyethyleneimine PEI solution (5 mg / mL) and 25 mL of 3M NaCl solution were added to a 1 L three-necked flask, placed in an ultrasonic cleaner, and mechanically stirred at 500 rpm. 100 mL of 800 nm silica microsphere solution obtained in step (1) was added dropwise to the PEI solution. Ultrasonication was performed for 45 minutes. The solution was centrifuged and washed 4 times at 8000 rpm for 5 minutes. Magnetic microspheres coated with positive electrolyte PEI were obtained.

[0063] 2) Add 200 mL of DMSA-modified Fe3O4 aqueous solution (10 mg / mL) and 25 mL of NaCl solution into a 1L three-necked flask, add 200 mL of microspheres obtained by centrifugation in the previous step into the Fe3O4 solution under ultrasonic stirring, stir at 500 rpm for 45 minutes, and wash the product by centrifugation at 8000 rpm for 5 minutes until the supernatant is colorless and transparent. A layer of Fe3O4-coated microspheres is obtained.

[0064] Repeat the above steps 1) and 2) until 5 layers of Fe3O4 are coated and dispersed in ultrapure water to obtain an aqueous solution of SiO2@Fe3O4 microspheres.

[0065] (4) Surface silica encapsulation:

[0066] 200mL ethanol, add 20mL Fe3O4 microsphere aqueous solution obtained in the previous step, stir at 300rpm for 15 minutes under ultrasound, add 5mL ammonia water, continue ultrasound for 15 minutes, add 10mL tetraethyl orthosilicate (TEOS), react in a 30℃ water bath, stir at 300rpm for 2 hours. The product is magnetically separated, washed 4 times with anhydrous ethanol and water respectively. Dispersed in anhydrous ethanol.

[0067] (5) Surface carboxyl modification:

[0068] 1) Surface amino modification (dimethylformamide DMF system)

[0069] Triaminopropyltriethoxysilane (APTES) was selected as the modified material. The microspheres obtained in the previous step were dispersed in 200 mL DMF, 5 mL ammonia water was added, and the mixture was stirred at 300 rpm for 15 minutes under ultrasound. 2 mL APTES was added and the mixture was stirred at 300 rpm at 30°C for 18 hours. Magnetic separation was performed, and the mixture was washed with anhydrous ethanol 4 times and water 4 times. The product was dispersed in pure water.

[0070] 3) Surface carboxyl modification (succinic anhydride)

[0071] 20 ml of amino balls obtained in the previous step were added to 100 mL of 5 mg / mL succinic anhydride in dimethylformamide DMF solution, and stirred at 500 rpm for 8 h in a 30° water bath. The particles were washed with ethanol and ultrapure water magnetic separation for 4 times to obtain the final product encapsulated silicon carboxyl magnetic microspheres, which were dispersed in pure water.

[0072] Example 3: This example provides a method for preparing 2 micron silica carboxyl magnetic microspheres, comprising the following steps:

[0073] (1) Preparation of 1.5 μm silica microsphere cores by seed growth method

[0074] In a 1000mL three-necked flask, take 12.5g of the ethanol suspension of 800nm ​​SiO2 microspheres prepared in Example 2 (the specific concentration needs to be calculated, about 7×10 9 SiO2 microspheres / L), add 422mL of ethanol, 3mL of deionized water and 75mL of ammonia water under mechanical stirring (speed 500rpm), totaling 500mL. Then, ammonia / water / ethanol mixed solution (62.5 / 35 / 60.5mL, totaling 158mL) and TEOS / ethanol mixed solution (162.5 / 87.5mL, totaling 250mL) were added dropwise at the same time, with a dropwise speed of 1mL / min. After the addition was completed, the reaction was continued for 2h. A 1.5μm silica microsphere core was obtained.

[0075] (2) Preparation of aqueous magnetic particles

[0076] 1) Preparation of oleic acid (OA)-coated magnetic particles (Fe3O4@OA) by coprecipitation

[0077] In a 250mL three-necked flask, add 50g of solid ferric chloride hexahydrate (FeCl3·6H2O), 150mL of ultrapure water, and 30g of solid ferrous sulfate heptahydrate (FeSO4·7H2O) in sequence, and stir ultrasonically to completely dissolve it. Heat in a water bath under nitrogen and condensed water conditions to 72°C. Pour in 80mL of ammonia water while stirring at 500rpm. React at 72°C for 30 minutes, add 15mL of oleic acid, continue to react for 30 minutes, then heat to 85°C and mature for 1 hour. After the product is cooled, it is magnetically separated, repeatedly washed with ethanol and ultrapure water, and dispersed in 200mL of n-hexane to form a stable magnetic fluid solution.

[0078] 2) Preparation of aqueous phase particles coated with dithiosuccinic acid (DMSA)

[0079] Add 320mL acetone, 220mL n-hexane, 2.5g DMSA to a 1000mL three-necked flask, stir to dissolve, then add 100mL of the oil phase magnetic particle solution prepared in the previous step. Place in a 60℃ water bath, stir at 500rpm, condense and reflux, and react for 4 hours. After the product is cooled, wash it 10 times with magnetic separation ultrapure water until the supernatant is clear. Disperse in 1L ultrapure water, add sodium hydroxide solution to adjust the pH to 10, and sonicate for 30 minutes to stabilize the pH at 10. Use dilute hydrochloric acid solution to adjust the pH to neutral, and sonicate for another 30 minutes. Pass through a 0.22μm filter membrane. Store at 4℃ away from light.

[0080] (3) Preparation of magnetic microspheres by layer-by-layer self-assembly method:

[0081] 1) Add 300 mL of polyethyleneimine PEI solution (5 mg / mL) and 25 mL of 3M NaCl solution into a 1 L three-necked flask, place in an ultrasonic cleaner, and mechanically stir at 500 rpm. Add 100 mL of 1.5 μm silica microsphere solution obtained in step (1) dropwise into the PEI solution. Ultrasonicate for 45 minutes. Centrifuge and wash 4 times at 8000 rpm for 5 minutes. Obtain magnetic microspheres coated with positive electrolyte PEI.

[0082] 2) Add 200 mL of DMSA-modified Fe3O4 aqueous solution (10 mg / mL) and 25 mL of NaCl solution into a 1L three-necked flask, add 200 mL of microspheres obtained by centrifugation in the previous step into the Fe3O4 solution under ultrasonic stirring, stir at 500 rpm for 45 minutes, and wash the product by centrifugation at 8000 rpm for 5 minutes until the supernatant is colorless and transparent. A layer of Fe3O4-coated microspheres is obtained.

[0083] Repeat the above steps 1) and 2) until 5 layers of Fe3O4 are coated and dispersed in ultrapure water to obtain an aqueous solution of SiO2@Fe3O4 microspheres.

[0084] (4) Surface silica encapsulation:

[0085] 200mL ethanol, add 20mL Fe3O4 microsphere aqueous solution obtained in the previous step, stir at 300rpm for 15 minutes under ultrasound, add 5mL ammonia water, continue ultrasound for 15 minutes, add 10mL tetraethyl orthosilicate (TEOS), react in a 30℃ water bath, stir at 300rpm for 2 hours. The product is magnetically separated, washed 4 times with anhydrous ethanol and water respectively. Dispersed in anhydrous ethanol.

[0086] (5) Surface carboxyl modification, using the positive and negative charge self-assembly method to alternately adsorb polyethyleneimine PEI and polyacrylic acid PAA:

[0087] 300mL polyethyleneimine PEI solution (5mg / mL) and 25mL 3M NaCl solution are added to a 1L three-necked flask, placed in an ultrasonic cleaner, and mechanically stirred at 500rpm. 100mL of the encapsulated silica magnetic microsphere solution obtained in 10g step (4) is added dropwise to the PEI solution. Ultrasonicate for 45 minutes. Magnetic separation and water washing are performed to obtain magnetic microspheres coated with positive electrolyte PEI. Subsequently, 100mL of the positively charged microspheres are added dropwise to 300mL of polyacrylic acid PAA solution and ultrasonically stirred for 45 minutes. Magnetic separation and water washing are performed to obtain the final product encapsulated silicon carboxyl magnetic microspheres, which are dispersed in pure water.

[0088] Comparative Example 1: This example provides a method for preparing 1 micron silica carboxyl magnetic microspheres without surface encapsulation, comprising the following steps:

[0089] (1) Preparation of 800 nm silica microsphere cores by seed growth method

[0090] In a 1000mL three-necked flask, first mix 252mL of methanol, 65mL of deionized water, and 20mL of ammonia water, and stir mechanically (speed 500rpm). Add 3.125g of the 400nm SiO2 microsphere suspension prepared in Example 1 (the specific concentration needs to be calculated, about 3×10 10 SiO2 microspheres / L). Then, under mechanical stirring and ultrasonic treatment, ammonia / water / methanol mixed solution (30.5 / 17.5 / 52mL, 100mL in total) and TEOS / methanol mixed solution (81.5 / 18.5mL, 100mL in total) were added dropwise using two syringe pumps, with a dropwise speed of 1ml / min. After the dropwise addition, the reaction was continued for 2h; after centrifugal washing, it was dispersed in ethanol. 800nm ​​silica microspheres were obtained.

[0091] (2) Preparation of aqueous magnetic particles

[0092] 1) Preparation of oleic acid (OA)-coated magnetic particles (Fe3O4@OA) by coprecipitation

[0093] In a 250mL three-necked flask, add 50g of solid ferric chloride hexahydrate (FeCl3·6H2O), 150mL of ultrapure water, and 30g of solid ferrous sulfate heptahydrate (FeSO4·7H2O) in sequence, and stir ultrasonically to completely dissolve it. Heat in a water bath under nitrogen and condensed water conditions to 72°C. Pour in 80mL of ammonia water while stirring at 500rpm. React at 72°C for 30 minutes, add 15mL of oleic acid, continue to react for 30 minutes, then heat to 85°C and mature for 1 hour. After the product is cooled, it is magnetically separated, repeatedly washed with ethanol and ultrapure water, and dispersed in 200mL of n-hexane to form a stable magnetic fluid solution.

[0094] 2) Preparation of aqueous phase particles coated with dithiosuccinic acid (DMSA)

[0095] Add 320mL acetone, 220mL n-hexane, 2.5g DMSA to a 1000mL three-necked flask, stir to dissolve, then add 100mL of the oil phase magnetic particle solution prepared in the previous step. Place in a 60℃ water bath, stir at 500rpm, condense and reflux, and react for 4 hours. After the product is cooled, wash it 10 times with magnetic separation ultrapure water until the supernatant is clear. Disperse in 1L ultrapure water, add sodium hydroxide solution to adjust the pH to 10, and sonicate for 30 minutes to stabilize the pH at 10. Use dilute hydrochloric acid solution to adjust the pH to neutral, and sonicate for another 30 minutes. Pass through a 0.22μm filter membrane. Store at 4℃ away from light.

[0096] (3) Preparation of magnetic microspheres by layer-by-layer self-assembly method:

[0097] 1) 300 mL of polyethyleneimine PEI solution (5 mg / mL) and 25 mL of 3M NaCl solution were added to a 1 L three-necked flask, placed in an ultrasonic cleaner, and mechanically stirred at 500 rpm. 100 mL of 400 nm silica microsphere solution obtained in step (1) was added dropwise to the PEI solution. Ultrasonication was performed for 45 minutes. The solution was centrifuged and washed 4 times at 8000 rpm for 5 minutes. Magnetic microspheres coated with positive electrolyte PEI were obtained.

[0098] 2) Add 200 mL of DMSA-modified Fe3O4 aqueous solution (10 mg / mL) and 25 mL of NaCl solution into a 1L three-necked flask, add 200 mL of microspheres obtained by centrifugation in the previous step into the Fe3O4 solution under ultrasonic stirring, stir at 500 rpm for 45 minutes, and wash the product by centrifugation at 8000 rpm for 5 minutes until the supernatant is colorless and transparent. A layer of Fe3O4-coated microspheres is obtained.

[0099] Repeat the above steps 1) and 2) to obtain microspheres coated with 5 layers of Fe3O, with a PEI layer on the surface, and then adsorb a layer of polyacrylic acid PAA to obtain unencapsulated silicon carboxyl magnetic beads, which are dispersed in ultrapure water.

[0100] Related detection characterization

[0101] Scanning electron microscope morphology inspection

[0102] Figure 3 Figure 4 Figure 5 Figure 6 The scanning electron microscope pictures of Examples 1, 2, 3 and Comparative Example 1 are shown. The microspheres have good dispersibility. The particle sizes of Examples 1, 2, and 3 are 500 nm, 1 μm, and 2 μm, respectively. There is no agglomeration or shedding of magnetic particles, and the surface magnetic particles are completely coated by the silicon layer. The surface of the microspheres with large particle sizes is smoother, and because the magnetic particles are smaller than the microspheres, it is easier to obtain a complete and continuous shell. The magnetic microspheres of Comparative Example 1 are not encapsulated, and the surface is magnetic particles. The microspheres also have a uniform particle size and no free magnetic particles.

[0103] Figure 7 SEPMAG Biomagnetic Separator Magnetic Performance Test

[0104] The Spanish SEPMAG biomagnetic separation device was used for magnetic responsiveness detection. The SEPMAG device can provide a uniform magnetic field to ensure stable separation conditions. It has monitoring functions and related software, which can monitor the magnetic separation process in real time and give a separation curve. In the curve, the index P reflects the slope of the curve, V0 is the minimum opacity when completely separated, reflecting whether there is magnetic residue, Vmax is the maximum opacity in the initial state, which can reflect the number, concentration, color and other properties of the magnetic beads, and T50 reflects the time taken for the magnetic separation to reach half of the maximum and minimum opacity. The slope and T50 depend on some characteristics derived from the magnetic beads (diameter, magnetic content%, magnetic material) and the suspension (buffer viscosity, magnetic bead concentration, etc.). It can be seen from the detection curve that the T50 time of Example 1 in water is 12.31 seconds, and the T99 time is 31 seconds, which can be completely separated within 31 seconds. The fitting variance of the curve is 0.998, indicating that the microspheres are well dispersed and there is no agglomeration and sedimentation.

[0105] Figure 8 The ninhydrin color reaction of amino magnetic microspheres modified with triaminopropyltriethoxysilane APTES, the intermediate product of Example 1

[0106] The amino modification effect of the intermediate product of Example 1 was detected by the ninhydrin colorimetric method. The steps are to prepare 10 mg / ml ninhydrin ethanol solution (prepared immediately before use), 200 μL amino balls and 200 μL ninhydrin solution, and heat at 80° for 10 minutes. On the left side of the figure are amino magnetic microspheres modified with the intermediate product APTES, and on the right side are carboxyl magnetic microspheres coated with polyacrylic acid PAA, the final product. It can be seen that the amino balls are obviously dark blue-purple. After modification, the amino groups are basically covered by carboxyl groups. The supernatant becomes colorless.

[0107] Fig. 9 The tetramethylbenzidine TMB color reaction results of Example 1 and Comparative Example 1 are shown in FIG.

[0108] Fe3O4 has peroxidase-like activity. The surface-exposed Fe3O4 will affect the chemiluminescent detection results of the horseradish peroxidase (HRP) system, limiting the application scenarios. It may also cause an increase in background due to non-specificity. The method of catalyzing TMB and hydrogen peroxide reaction to develop color is used to detect whether the coating is complete. From the result figure, it can be seen that the unencapsulated comparative example 1 on the left is obviously blue, and the magnetic particles on the right are not exposed after encapsulation, and no color development occurs.

[0109] Evaluation of the application of Examples 1, 2, 3 and Comparative Example 1 on the CA242 chemiluminescence platform

[0110] The magnetic microspheres of Examples 1, 2, and 3 of the present invention were applied to the field of chemiluminescent immunoassay, and the application performance of the magnetic microspheres of the present invention and commercially available imported magnetic microspheres were compared. Under the same coupling conditions, the CA242 antibody was bound to the magnetic microspheres of the present invention and the commercially available magnetic microspheres. The machine model used was Yingkai i2910. Reagent components: M, silica-based magnetic beads. R1, biotin-labeled antibody CA242-SL1-Bio. R2, AE-labeled antibody: CA242-RM0799-AE calibrator 0, 0.5, 2.5, 10, 20, 30 U / mL 6 points, calibrator (antigen from Conaiger)

[0111] Detection process, delayed one-step sandwich method: sample + R1 + R2 → incubate for 15 minutes → + M → incubate for 5 minutes → wash 3 times

[0112] →+substrate→detection. The detection results are shown in Table 1:

[0113] Table 1 Chemiluminescence detection results of Examples 1, 2, 3, Comparative Example 1 and imported magnetic beads of reference substance

[0114]

[0115] From the test results in the above table, it can be seen that the background values ​​of Examples 1, 2, and 3 are slightly lower than the imported products of the control, the luminescence values ​​of high concentrations are higher than those of the control, and the overall signal-to-noise ratio is higher than that of the control. This shows that the silicon carboxyl magnetic microspheres obtained by the present invention have good sensitivity and linear range in chemiluminescence applications, and can replace imported products. The performance of the unencapsulated carboxyl magnetic beads in Comparative Example 1 is also close to that of the control, but the nonspecificity is slightly higher and the overall chemiluminescence intensity is slightly lower. From the application results, it can be seen that surface encapsulation can effectively reduce nonspecificity and improve detection sensitivity.

[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all fall within the protection scope of the present invention.

Claims

1. A method for preparing silicon-based magnetic beads, characterized in that: The following steps are involved: (1) Preparation of the core of silica microspheres; (2) Preparation of aqueous phase particles coated with dithiosuccinic acid (DMSA); (3) Preparation of magnetic microspheres by layer-by-layer self-assembly method; (4) Surface silica encapsulation; (5) Surface carboxyl modification to obtain silica-based magnetic beads.

2. The preparation method according to claim 1, characterized in that: The step (1) of preparing the inner core of the silica microspheres comprises: The silica microspheres are prepared by the seed growth method and the sintering method; the particle size of the silica microspheres is 200nm-3μm.

3. The preparation method according to claim 2, characterized in that: The particle size of the silica microspheres is 400nm-1.5μm.

4. The preparation method according to claim 3, characterized in that: The preparation of aqueous phase particles in step (2) includes preparing oleic acid-coated magnetic particles and DMSA-coated aqueous phase particles by coprecipitation. The coprecipitation method for preparing oleic acid-coated magnetic particles includes mixing and dissolving ferric chloride hexahydrate, ultrapure water, and ferrous sulfate heptahydrate, heating the mixture to 70-75° C., adding ammonia water, keeping the mixture warm for 20-60 min, adding oleic acid, continuing the reaction for 20-60 min, heating the mixture to 80-85° C., aging the mixture for 1-2 h, magnetically separating the product, and dispersing the product in n-hexane to form a 50-100 mg / mL magnetic fluid solution.

5. The preparation method according to claim 4, characterized in that: The preparation of the DMSA-coated aqueous phase particles comprises the steps of mixing acetone, n-hexane and DMSA-coated aqueous phase particles, adding an oleic acid-coated magnetic particle fluid solution, refluxing for 4-5 hours, magnetically separating the product, dispersing it in ultrapure water, adjusting the pH to 9.5-10, ultrasonicating for 20-60 minutes, adjusting the pH to neutral, ultrasonicating for 20-60 minutes, filtering, and obtaining the DMSA-coated aqueous phase particles.

6. The preparation method according to claim 5, characterized in that: In the step (3), the layer-by-layer self-assembly method for preparing magnetic microspheres includes 1) mixing the 5-10 mg / mL polyethyleneimine aqueous solution with the 3M NaCl solution, adding the silica microsphere core aqueous solution of step (1) thereto, ultrasonicating for 30-60 minutes, centrifuging and washing with water, to obtain positive electrolyte-coated magnetic microspheres.

7. The preparation method according to claim 6, characterized in that: In the step (3), the layer-by-layer self-assembly method for preparing magnetic microspheres also includes the step 2) of mixing DMSA-coated aqueous particles with 3M NaCl solution, adding the mixture to the positive electrolyte-coated magnetic microspheres, ultrasonicating at 400-500 rpm for 20-60 min, centrifuging and washing with water to obtain one layer of Fe3O4-coated microspheres, repeating the above steps 1) and 2) until 5 layers of Fe3O4 are coated, thereby obtaining magnetic microspheres prepared by the layer-by-layer self-assembly method.

8. The preparation method according to claim 7, characterized in that: The surface silica encapsulation in step (4) comprises adding ammonia water and tetraethyl orthosilicate (TEOS) to the magnetic microspheres obtained in step (3), reacting at 20-35° C. for 2-2.5 hours, and magnetically separating to obtain a surface silica encapsulated product.

9. The preparation method according to claim 8, characterized in that: In the step (5), the surface carboxyl modification also includes surface amino modification before the surface carboxyl modification, and the surface amino modification material is one or more of triaminopropyltriethoxysilane and polyethyleneimine PEI; the surface carboxyl modification includes coupled polyacrylic acid PAA and succinic anhydride modification.

10. Use of the silica-based magnetic beads obtained according to the preparation method according to any one of claims 1 to 9 in CA242 chemiluminescence platform, nucleic acid extraction, and DNA fragment sorting.